Coupling plasma physics and chemistry in the PIC model of electric propulsion: Application to an air-breathing, low-power Hall thruster - Taccogna, Francesco; Cichocki, Filippo; Minelli, Pierpaolo (Frontiers in Physics, 2022)
This work represents a first attempt to include the complex variety of electron-molecule processes in a full kinetic Particle-in-Cell / Test Particle Monte Carlo model for the plasma and neutral gas phase in a Hall thruster. Particular emphasis has been put on earth's atmosphere species for the air-breathing concept. The coupling between the plasma and the gas phase is self-consistently captured by assuming the cold gas approximation and taking into account gas-wall and gas recycling from the walls due to ion neutralization. Results show that, with air molecular propellants, all the most relevant thruster performances are degraded with respect to the Xe propellant nominal case. The main reasons can be ascribed to a reduced ionization cross section, a larger gas ionization mean free path due to lighter mass air species and to the additional electron collisional power losses. While vibrational excitations power losses are negligible, dissociation and electronic excitations compete with the ionization channel. In addition, for molecular oxygen, the dissociation leads to even faster atoms further reducing their transit time inside the discharge channel. Further studies are needed to investigate the role of non-equilibrium vibrational kinetics and mestastable states for stepwise ionization.